2024
DOI: 10.3390/microorganisms12020289
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Silver Nanoparticles Mixed with Calcium Hydroxide against Candida albicans: An Ex Vivo Analysis

Maha Alghofaily,
Jood Alfraih,
Aljohara Alsaud
et al.

Abstract: Introduction: The purpose of this study was to assess the antifungal activity of silver nanoparticles (AgNPs) in combination with calcium hydroxide (Ca(OH)2) against Candida albicans (C. albicans). Methods: AgNPs was mixed with pure Ca(OH)2 powder in an aqueous base. A standard suspension (1 × 108 bacterial cells/mL) of C. albicans was prepared in a 96-well plate and incubated on shaker at 37 °C in 100% humidity to allow fungal biofilm formation in infected dentin slices (n = 98). The minimum inhibitory concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Teja et al explored the additive effects of various nanoparticles combined with Ca(OH) 2 on E. faecalis biofilms, concluding that AgNP incorporation into Ca(OH) 2 showcased superior efficacy [ 176 ]. Accumulating studies have also demonstrated that AgNPs mixed with Ca(OH) 2 present more pronounced antibiofilm effects against E. faecalis , C. albicans , F. nucleatum , and even multispecies biofilms compared to Ca(OH) 2 [ 177 , 178 , 179 , 180 ]. The combination of NPs with Ca(OH) 2 can bring about additive or synergistic effects on root canal disinfection.…”
Section: The Application Of Nanomaterials Used In Endodonticsmentioning
confidence: 99%
“…Teja et al explored the additive effects of various nanoparticles combined with Ca(OH) 2 on E. faecalis biofilms, concluding that AgNP incorporation into Ca(OH) 2 showcased superior efficacy [ 176 ]. Accumulating studies have also demonstrated that AgNPs mixed with Ca(OH) 2 present more pronounced antibiofilm effects against E. faecalis , C. albicans , F. nucleatum , and even multispecies biofilms compared to Ca(OH) 2 [ 177 , 178 , 179 , 180 ]. The combination of NPs with Ca(OH) 2 can bring about additive or synergistic effects on root canal disinfection.…”
Section: The Application Of Nanomaterials Used In Endodonticsmentioning
confidence: 99%